Modelling and prognostication of growth in the number of patients treated for neovascular age‐related macular degeneration. Issue 8 (18th February 2021) - Potapenko, Ivan; la Cour, Morten
Abstract: Purpose: The number of patients receiving anti‐VEGF therapy has increased rapidly since its introduction in Denmark in 2007, placing an enormous pressure on the public healthcare system. In this study, we attempt to describe this growth and identify the factors driving it. Methods: Data on treatment of the entire population of neovascular AMD patients in the Capital Region of Denmark between 2007 and 2019 was retrieved. The age and sex standardized incidences of first time treatment and changes in duration of treatment were analysed. Results: The number of patients in active treatment increased from 576 in 2007 to 3684 in 2019. The growth was initially driven by accumulation of patients continuing anti‐VEGF therapy for extended periods of time (259 patients/year). As larger numbers of patients began to be discharged, the increase slowed to 181 patients/year in late 2010s, with demographic change becoming the main growth driving factor. The incidence of first treatment increased slightly during the study period, mainly for individuals over 85 years. For patients under 85 years, treatment incidences closely followed neovascular AMD incidences from population studies. The likelihood of remaining in anti‐VEGF treatment after the initial injection followed exponential decay curve ( t 1/2  = 3.6 years). Based on this observation, a model was created to describe the number of patients in active treatment, which accurately described historical data ( R 2  = 0.999), and forecast a linear growth of 138 patients/year until 2030. Conclusion: Treatment incidences and modelling reported in this study might facilitate a more informed and accurate planning of future ophthalmology services.